Transnational Caregiving and End-of-Life in Older Japanese Americans in the United States and Japan, in Collaboration with AI (Artificial Intelligence) and Robots - Hoshino, Kazumi (Bulletin of Asia-Pacific Studies, 2025)
This research examines narratives of older Japanese Americans who were over 64 years old and experienced transnational caregiving for the oldest old parents (over 79 years old) with ICT, AI (Artificial Intelligence), and robots in the U.S. and Japan. Second, the study proposes policy implications of transnational caregiving and end-of-life, in collaboration with ICT, AI (Artificial Intelligence), and robots. In-person interviews with older Japanese Americans were conducted in California. As a result of a content analysis, the research presents policy implications; 1) Develop AI (Artificial Intelligence) and robots for transnational caregiving and end-of-life; 2) Support wellness in older Japanese American transnational caregivers through AI and robots; and 3) Protect against discrimination against Asian Americans and Asians by AI and robots.